2018
DOI: 10.3390/rs10020287
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Temporal InSAR Structural Damage Assessment: The London Crossrail Case Study

Abstract: Spaceborne multi-temporal interferometric synthetic aperture radar (MT-InSAR) is a monitoring technique capable of extracting line of sight (LOS) cumulative surface displacement measurements with millimeter accuracy. Several improvements in the techniques and datasets quality led to more effective, near real time assessment and response, and a greater ability of constraining dynamically changing physical processes. Using examples of the COSMO-SkyMed (CSK) system, we present a methodology that bridges the gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 38 publications
0
88
0
Order By: Relevance
“…The first application of the InSAR was the monitoring of an earthquake in Landers, California [20], but the temporal resolution was relatively low because of the absence of analyzing on time series images. To overcome this limitation, multi-temporal InSAR was introduced for long-term and large-scale monitoring of surface deformation [21,22]. More specifically, a permanent scatterers InSAR (PS-InSAR) method proposed by Ferretti et al and a small baseline subset InSAR (SBAS-InSAR) method introduced by Berardino et al have been widely used in related fields with millimetric accuracy [23][24][25].…”
mentioning
confidence: 99%
“…The first application of the InSAR was the monitoring of an earthquake in Landers, California [20], but the temporal resolution was relatively low because of the absence of analyzing on time series images. To overcome this limitation, multi-temporal InSAR was introduced for long-term and large-scale monitoring of surface deformation [21,22]. More specifically, a permanent scatterers InSAR (PS-InSAR) method proposed by Ferretti et al and a small baseline subset InSAR (SBAS-InSAR) method introduced by Berardino et al have been widely used in related fields with millimetric accuracy [23][24][25].…”
mentioning
confidence: 99%
“…Multitemporal InSAR processing has been employed with high accuracy in other studies. For example, the use of persistent scatterers to track surface deformation and associated damage in urban environments, e.g., [34]. While a multitemporal InSAR approach using methods such as persistent scatterers provides insightful and accurate results, it requires that data collection and processing be performed after the event has occurred.…”
Section: Advancements and Improvements Using Time Series Of Coherencementioning
confidence: 99%
“…When it is determined that an urban bridge has damage or potential damage, it is always important to seek the cause or causes of the damage, so that monitoring can be used for future preventative maintenance of the bridge. Relevant studies have shown that the causes of urban bridge damage are often closely related to the surrounding environment [26,27]. Differential Interferometry Synthetic Aperture Radar (D-InSAR) is a technique that obtains large-scale surface micro-deformation information from space [28].…”
Section: Introductionmentioning
confidence: 99%